First adult record, redescription and distribution of Stemonosudis elongata (Aulopiformes: Paralepididae) - Ho, Hsuan-Ching; Huang, Chih-Hsiung (Zootaxa, 2022)
The original description of Macroparalepis elongatus Ege, 1933 (family Paralepididae) was based on a young specimen taken from Sri Lanka. No adult information is available since it was described. Six additional specimens, including three adults and three young specimens, were found in the museum collections. The adult morphology is described for the first time and its distribution range is now extended to South Pacific Ocean off New Caledonia and Australia, and the Western Indian Ocean off Madagascar. Detailed description and comparison of these specimens and the holotype, as well as a revised diagnosis for the species, are provided.